Open Fermentative Production of L-Lactic Acid from Distillers’ Grains by Lactobacillus casei CICC 6056 - Jin Zheng; Yingying Liu; Xiaohong Sun; Qunhui Wang; Hui Zou; Juan Wang; Ming Gao (BioResources, 2016)
Distillers’ grains (DG) are potential fermentable sugar substrates for the production of value-added products. This study focused on the development of an open fermentation process for the production of L-lactic acid from DG using Lactobacillus casei CICC 6056. The open fermentation process was feasible, resulting in an L-lactic acid yield similar to that obtained with sterilized fermentation. However, a decrease in pH below 5.0 after 24 h resulted in a poor L-lactic acid concentration of 9.18 g/L and an inferior reducing sugar conversion rate of 53.6%. Therefore, an optimal pH adjustment method was sought. A pH adjustment to 6.5 every 24 h effectively improved the L-lactic acid concentration to 21.3 g/L with a 97.8% reducing sugar conversion rate. Furthermore, the application of a simultaneous saccharification and fermentation process at 50 °C in open condition increased the L-lactic acid concentration to 25.0 g/L. This yield was superior to L-lactic acid fermentation from DG using a separate hydrolysis and fermentation method (21.3 g/L) and from a commercial sugar in batch culture (23.6 g/L). These results demonstrated that L. casei CICC 6056 has great industrial potential as a superior candidate strain for the production of L-lactic acid from DG due to its broad applicability in a wide temperature range (from 37 to 50 °C).